Incidence and Patient Profile of Carcinoma Breast Patients Presenting in Surgical OPD in a Tertiary Care Hospital (Faridpur Medical College Journal, 2021)
Breast cancer is one of the common cancers in women that causes financial health burden and or death in Bangladesh. Economically we are slowly rising from low to middle income country, which is changing our women's lifestyle. Risk factors of breast cancer include lifestyle factors like- age at first childbirth, parity, using oral contraceptives, BMI; which are also changing in our women. This study will look at our current incidence and patient profile of breast cancer patient. This is a retrospective study done in BIRDEM General Hospital. One hundred patient presenting with breast lump during the period of September 2018 -May 2019 were selected by purposive sampling. In